1991
DOI: 10.1038/352085a0
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an improved baculovirus insecticide containing an insect-specific toxin gene

Abstract: Baculoviruses provide alternatives to chemicals for controlling insect pests and can be applied by spraying. Baculoviruses have a limited host range, but work relatively slowly. They are dissolved in the midgut of insect larvae to release infectious virions which enter gut epithelial cells and begin to replicate. Replication in other organs causes extensive tissue damage and eventually death. This process can take 4-5 days, but in the field may last for more than a week, allowing the larvae to feed for longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
160
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 334 publications
(166 citation statements)
references
References 25 publications
5
160
1
Order By: Relevance
“…2,3,4 and Tables 1 and 2). Previous studies reported that baculovirus-directed functional expression of the excitatory anti-insect selective scorpion toxin AaIT fused to a signal peptide coding sequences of an insect protein bombyxin or of the baculovirus protein gp67 [12][13][14]. In the present study, we demonstrate that expression, secretion and correct processing of LqhcdT can be achieved by direct cloning of its cDNA, including the LqhczIT signal peptide coding sequences.…”
Section: Discussionsupporting
confidence: 55%
“…2,3,4 and Tables 1 and 2). Previous studies reported that baculovirus-directed functional expression of the excitatory anti-insect selective scorpion toxin AaIT fused to a signal peptide coding sequences of an insect protein bombyxin or of the baculovirus protein gp67 [12][13][14]. In the present study, we demonstrate that expression, secretion and correct processing of LqhcdT can be achieved by direct cloning of its cDNA, including the LqhczIT signal peptide coding sequences.…”
Section: Discussionsupporting
confidence: 55%
“…This is shortened with the parental baculovirus infection to about 7 days and to 5-6 days with recombinant SPx baculovirus. Similar results have been obtained with recombinant baculoviruses expressing neurotoxins of the scorpion A. australis or the mite Pyemotes tritici 5 [6,7,49]. We think that further improvements could be obtained by adjusting the secretion pathway to imitate the native one.…”
Section: Discussionsupporting
confidence: 79%
“…The two helices have quite different characters. The first, PLLILGS (3)(4)(5)(6)(7)(8)(9), is apolar, whereas the second, IQ-AIHDAQR (17)(18)(19)(20)(21)(22)(23)(24)(25), contains polar and charged amino acids. This will result in different interactions with cell membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Baculoviruses have long been used as biopesticides 3,4 and recombinant protein expression systems. 5,6 Recent research has focused on the use of baculoviruses as vectors in gene therapy because of (1) their ability to infect, but not replicate in, mammalian cells; (2) their low cytotoxicity; and (3) their ability to carry large foreign genes into their genome.…”
Section: Introductionmentioning
confidence: 99%